The Impact of Planning on Employee Productivity at PT Narindo Solusi Telekomunikasi in Gunungsitoli City - Ndraha, Defirman; Waruwu, Sukaaro; Hulu, Fatolosa; Waruwu, Meiman Hidayat (ProBisnis : Jurnal Manajemen, 2024)
This study aims to determine the effect of planning on employee productivity at PT. Narindo Solusi Telekomunikasi in Gunungsitoli City. Trust can be observed in situations where a partner or employee carries out their duties. This research employs a descriptive method with a quantitative approach, utilizing questionnaires for data collection. The population in this study consists of the employees of PT. Narindo Solusi Telekomunikasi in Gunungsitoli City from April to September 2012. The sampling was done using a random sampling technique, setting the sample size at 50% of the 100 employees in the population. Data analysis was performed using simple linear regression analysis. The results of this study indicate that planning has a positive and significant effect on employee loyalty (t-value = 7.014 > t-table = 2.006). The regression coefficient analysis result of 0.234, which is positive, indicates that the higher the performance planning, the higher the employee loyalty. The coefficient of determination is 0.562, meaning that 52.6% of the variance in the dependent variable (Performance Productivity) can be explained by the independent variable (Planning). Meanwhile, 47.4% of the variance in the dependent variable (Performance Productivity) is explained by other factors not examined in this study. To increase employee loyalty, the owner of PT. Narindo Solusi Telekomunikasi in Gunungsitoli City must maintain and enhance trust in employees so that the existing employees remain loyal and do not easily move to other companies.